Quick-strength high-toughness asphalt and preparation method thereof
By optimizing raw material ratio and introducing inorganic fillers and anti-flaking agents, and adopting advanced preparation processes, the limitations of traditional asphalt materials in terms of strength, toughness and construction speed are solved, and high-strength, high-toughness and rapid curing asphalt materials are achieved, which improves the bearing capacity and service life of the road.
Patent Information
- Application Number
- CN202411711509.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional asphalt materials have limitations in strength, toughness and construction speed, which is difficult to meet the high requirements of modern transportation for road materials. At the same time, the modified asphalt has problems such as unreasonable raw material ratio, complex process and uneven dispersion of modifiers during the preparation process, resulting in limited modification effect and high cost.
By optimizing the raw material ratio, inorganic fillers and anti-flaking agents are introduced, and advanced preparation processes are adopted, including ball mill grinding, silane coupling agent modification and high-temperature calcination, the high strength, high toughness and rapid curing of asphalt materials are achieved.
The high strength, high toughness and rapid curing of asphalt materials are achieved, which improves the load-bearing capacity and service life of the road, while simplifying the preparation process and reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified asphalt preparation, and relates to a quick-strengthening and high-toughness asphalt and a preparation method thereof. Background Art
[0002] In road construction and maintenance, asphalt is an important building material, and its performance directly affects the durability and safety of the road. Traditional asphalt materials have certain limitations in strength, toughness and construction speed, and it is difficult to meet the high requirements of modern transportation for road materials. Therefore, the development of a fast-strengthening and high-toughness asphalt to improve the bearing capacity and service life of the road has important practical significance and application value.
[0003] At present, there are some modified asphalt products on the market, such as SBS modified asphalt, OPE modified asphalt, etc. These products have improved the performance of asphalt to a certain extent. However, these modified asphalts often have problems such as unreasonable raw material ratio, complex preparation process, and uneven dispersion of modifiers during the preparation process, resulting in limited modification effect and high cost. In addition, some modified asphalts are prone to peeling and cracking during long-term use, affecting the stability and safety of the road.
[0004] In view of the above problems, the present invention proposes a new fast-strengthening high-toughness asphalt and a preparation method thereof. The asphalt optimizes the raw material ratio, introduces special components such as inorganic fillers and anti-stripping agents, and adopts advanced preparation technology to achieve high strength, high toughness and rapid curing of asphalt materials, effectively improving the bearing capacity and service life of the road. At the same time, the preparation method of the present invention is simple and efficient, easy to industrialize, and has broad market application prospects. Summary of the invention
[0005] The purpose of the present invention is to provide a fast-strengthening and high-toughness asphalt and a preparation method thereof, which has the characteristics of good performance.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A fast-strengthening high-toughness asphalt, wherein the raw materials for preparing the fast-strengthening high-toughness asphalt are as follows: by mass percentage, 75-85% of base asphalt, 5-12% of polystyrene butadiene copolymer SBS, 3-8% of oxidized polyethylene OPE, 2-5% of inorganic filler, 1-3% of anti-stripping agent, and 2-6% of rubber oil; The preparation method of the inorganic filler is as follows: S1.1: Quartz sand and limestone powder were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A; S1.2: The polyester fiber and the PLA fiber were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture B; S1.3: Mix mixture A and mixture B in a mass ratio of (1-3):1, disperse in 30-50% by mass fraction of silane coupling agent KH550, with a solid-liquid mass ratio of 1:1, add 1wt% polyethylene glycol, stir at a speed of 200r / min, raise the temperature to 50℃ while stirring, continue stirring for 0.5h after constant temperature, filter, and dry at 80℃ for 16h to obtain mixture C; S1.4: The mixture C is transferred to 200°C and calcined for 2h. After slowly cooling to room temperature, it is ground again to obtain an inorganic filler with a particle size of 500 mesh.
[0007] Furthermore, the base asphalt is No. 70 petroleum asphalt.
[0008] Furthermore, the preparation method of the anti-stripping agent is as follows: rosin, beeswax and terpene resin are mixed in a mass ratio of 1:1:1, heated to 110°C, stirred at 150r / min after constant temperature, and the stirring time is 1h, 2wt% silane coupling agent KH550 is added, and stirring is continued for 0.5h to obtain the anti-stripping agent.
[0009] Furthermore, the particle size of the mixture A in S1.1 is 200 mesh.
[0010] Furthermore, the particle size of the mixture B in S1.2 is 200 mesh.
[0011] Furthermore, the number average molecular weight of the polyethylene glycol added in S1.3 is in the range of 2000 to 4000.
[0012] Furthermore, the slow cooling rate in S1.4 is 2°C / min.
[0013] A method for preparing a fast-strengthening high-toughness asphalt, the method for preparing the fast-strengthening high-toughness asphalt is as follows: S2.1: Heat the base asphalt to 135-155°C and stir at a speed of 4500-5500 r / min for 1-2 h; S2.2: Add SBS and OPE in proportion, increase the speed to 8000r / min, and slowly increase the temperature to 180~185℃, and stir for 0.5~1h after constant temperature; S2.3: After stirring, slowly cool to 170~175℃, add inorganic filler, increase the speed to 10000r / min and continue stirring for 2~3h. After high-speed stirring, adjust the speed to 800r / min, add anti-stripping agent, stir at a constant temperature of 170~175℃ for 1~2h to obtain the quick-strength and high-toughness asphalt.
[0014] Furthermore, the rate of slow heating in S2.2 is 2°C / min.
[0015] Furthermore, the slow cooling rate in S2.3 is 1°C / min.
[0016] SBS in the present invention was purchased from Guangdong Shengke Biochemical Technology Co., Ltd. with a purity of AR; OPE in the present invention was purchased from Zhongshan Yuanda New Materials Co., Ltd. with a purity of 99%; polyester fiber in the present invention was purchased from Hubei Longxin Chemical Industry Co., Ltd. with a purity of 98%; PLA fiber in the present invention was purchased from Beijing Thompson Biotechnology Co., Ltd. with a purity of 98%; rosin in the present invention was purchased from Shenyang Elepux Chemical Co., Ltd. with a purity of 99%; beeswax in the present invention was purchased from Shaanxi Panier Biotechnology Co., Ltd. with a purity of 100%; terpene resin in the present invention was purchased from Shenyang Elepux Chemical Co., Ltd. with a purity of 99%; rubber oil in the present invention was purchased from Hubei Zhonglong Kangsheng Fine Chemical Co., Ltd. with a purity of 99%.
[0017] The present invention adopts No. 70 petroleum asphalt as the basic material, which has good physical and chemical properties, such as suitable viscosity, good adhesion and plasticity, etc., and provides a basis for preparing high-performance fast-strengthening and high-toughness asphalt.
[0018] SBS and OPE are then added in proportion. These two polymer materials can significantly improve the strength and toughness of asphalt, while giving asphalt better elasticity and recovery ability, allowing the road to better withstand the crushing and impact of heavy-loaded vehicles.
[0019] The present invention compounds inorganic materials such as quartz sand, limestone powder, polyester fiber and PLA fiber into inorganic fillers, and grinds the inorganic fillers to have a moderate particle size and uniform distribution, thereby enhancing the overall stability and durability of the asphalt mixture.
[0020] The addition of inorganic fillers can significantly improve the compressive strength, tensile strength and toughness of asphalt mixtures, allowing roads to withstand greater loads and deformations; inorganic fillers can improve the water stability and thermal stability of asphalt mixtures, reduce road damage caused by moisture erosion and temperature changes, and extend the service life of roads; inorganic fillers can adjust the viscosity of asphalt mixtures, making construction smoother, while improving the flatness and density of the road surface.
[0021] In the present invention, quartz sand and limestone powder are used as the main part of the inorganic filler to provide hardness and strength support. Quartz sand and limestone powder have high hardness and wear resistance, which can increase the compressive strength and wear resistance of asphalt mixture. At the same time, they have strong adhesion with asphalt, which helps to form a compact structure. The addition of polyester fiber and PLA fiber can enhance the toughness and crack resistance of asphalt mixture, because polyester fiber and PLA fiber have high tensile strength and elongation at break, can form a physical cross-linking structure in asphalt mixture, and improve the overall toughness and crack resistance. In addition, the addition of fiber can also improve the rheological properties of asphalt mixture, making the construction smoother; the present invention uses silane coupling agent KH550 to improve the compatibility between inorganic filler and asphalt. Silane coupling agent KH550 has the characteristics of being inorganic-friendly at one end and organic-friendly at the other end, and can form a chemical bond between the inorganic filler and asphalt, thereby improving the compatibility and adhesion between them, which helps to form a more compact and stable structure; polyethylene glycol is used to adjust the dispersibility and stability of the inorganic filler. Polyethylene glycol is a polymer compound with good dispersibility and stability. It can be adsorbed on the surface of the inorganic filler to form a protective film to prevent the inorganic filler from agglomerating and settling in the asphalt. At the same time, polyethylene glycol can also improve the compatibility between the inorganic filler and asphalt.
[0022] In the preparation process of the inorganic filler of the present invention, the polyester fiber and the PLA fiber are firstly ground at high speed in a ball mill to make the fiber surface rough, which increases the contact area and interaction force between the fibers. This interaction force mainly comes from the physical entanglement and chemical bonding between the fiber molecular chains. During the grinding process, the fiber molecular chains are partially broken, generating free radicals or active end groups, which can react with the active groups on other fiber molecular chains to form chemical bonds, thereby enhancing the cross-linking effect between the fibers; after adding the silane coupling agent, one end of the silane coupling agent chemically reacts with the functional groups such as hydroxyl groups on the surface of the inorganic filler to form chemical bonds; the other end can react with the active groups on the surface of the polyester fiber and the PLA fiber, thereby tightly connecting the inorganic filler and the fiber.
[0023] The present invention also adds an anti-stripping agent to further improve the performance of asphalt. Rosin, as a natural resin, has excellent adhesion and wettability. In the anti-stripping agent, rosin can enhance the adhesion between asphalt and aggregate, thereby improving the anti-stripping performance of asphalt mixture. This is because the polar functional groups carboxyl and hydroxyl in the rosin molecules can chemically react or physically adsorb with the functional groups on the surface of asphalt and aggregate to form a strong bond; beeswax has excellent lubricity and water resistance. In the anti-stripping agent, beeswax can improve the construction performance of asphalt mixture, reduce the friction resistance between aggregates, and improve the water stability of asphalt mixture. The long-chain hydrocarbon groups in the beeswax molecules can form a lubricating film to reduce friction and wear between aggregates. At the same time, the hydrophobic groups in beeswax can prevent moisture from invading the interior of the asphalt mixture, thereby improving its water stability; terpene resin is a thermoplastic resin with excellent flexibility and heat resistance. Among anti-stripping agents, terpene resin can enhance the flexibility and heat resistance of asphalt mixtures, reduce cracking and peeling caused by temperature changes, and the aromatic and aliphatic hydrocarbon groups in the terpene resin molecules can form a cross-linked network structure to improve the cohesion and shear strength of asphalt mixtures. At the same time, the heat resistance of terpene resin can resist deformation and flow at high temperatures, thereby maintaining the stability of asphalt mixtures.
[0024] In the anti-stripping agent, rosin, beeswax, terpene resin and silane coupling agent KH550 form a good synergistic effect. They work together in the asphalt mixture to improve the adhesion between asphalt and aggregate, construction performance, water stability, and flexibility and heat resistance.
[0025] Rosin and silane coupling agent KH550 work together to enhance the adhesion between asphalt and aggregate. Rosin provides polar functional groups to chemically react or physically adsorb with asphalt and aggregate; silane coupling agent KH550 acts as a bridge molecule to connect inorganic fillers and organic asphalt molecules, further improving adhesion; the lubricating effect of beeswax reduces the friction resistance between aggregates and improves the construction performance of asphalt mixture. At the same time, the hydrophobicity of beeswax improves the water stability of asphalt mixture; the flexibility and heat resistance of terpene resin enhance the flexibility and heat resistance of asphalt mixture. The cross-linked network structure in the terpene resin molecules improves the cohesion and shear strength of the asphalt mixture; at the same time, its heat resistance can resist deformation and flow at high temperatures.
[0026] Beneficial effects of the present invention: (1) The various components in the inorganic filler of the present invention work together to improve the performance of the asphalt mixture through synergistic effects. Quartz sand and limestone powder provide hardness and strength support, polyester fiber and PLA fiber enhance toughness and crack resistance, silane coupling agent KH550 improves compatibility, and polyethylene glycol adjusts dispersibility and stability. These components complement and promote each other, so that the inorganic filler can play the maximum effect in the asphalt mixture; (2) The present invention also adds an anti-stripping agent to further improve the performance of asphalt. In the anti-stripping agent, rosin, beeswax, terpene resin and silane coupling agent KH550 form a good synergistic effect. They work together in the asphalt mixture to improve the performance of asphalt. DETAILED DESCRIPTION
[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0028] Raw material ratio 1: No. 70 petroleum asphalt 75%, SBS 6%, OPE 5%, inorganic filler 5%, anti-stripping agent 3%, rubber oil 6%; Raw material ratio 2: No. 70 petroleum asphalt 85%, SBS 5%, OPE 3%, inorganic filler 2%, anti-stripping agent 3%, rubber oil 2%; Raw material ratio 3: No. 70 petroleum asphalt 75%, SBS 12%, OPE 8%, inorganic filler 2%, anti-stripping agent 1%, rubber oil 2%.
[0029] Example 1 The preparation method of the inorganic filler is as follows, S1.1: Quartz sand and limestone powder were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A, wherein the particle size of the mixture A was 200 mesh; S1.2: The polyester fiber and the PLA fiber were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture B, wherein the particle size of the mixture B was 200 mesh; S1.3: Mix mixture A and mixture B in a mass ratio of 2:1, disperse in 40% by mass fraction of silane coupling agent KH550, with a solid-liquid mass ratio of 1:1, add 1wt% polyethylene glycol 2000, stir at a speed of 200r / min, raise the temperature to 50℃ while stirring, continue stirring for 0.5h after constant temperature, filter, and dry at 80℃ for 16h to obtain mixture C; S1.4: Transfer the mixture C to 200°C and roast for 2h. Slowly cool it to room temperature and grind it again at a cooling rate of 2°C / min to obtain an inorganic filler with a particle size of 500 mesh.
[0030] The preparation method of the anti-stripping agent is as follows: Rosin, beeswax and terpene resin were mixed in a mass ratio of 1:1:1, heated to 110°C, stirred at 150 r / min after constant temperature, and stirred for 1 hour. 2 wt% of silane coupling agent KH550 was added, and stirring was continued for 0.5 hours to obtain the anti-stripping agent.
[0031] A method for preparing a fast-strengthening high-toughness asphalt, the method for preparing the fast-strengthening high-toughness asphalt is as follows: S2.1: Heat the base asphalt to 145°C and stir at a speed of 5000 r / min for 2 h; S2.2: Add SBS and OPE in proportion, increase the speed to 8000r / min, and slowly increase the temperature to 185℃ at a rate of 2℃ / min. Stir for 0.5h after constant temperature. S2.3: After stirring, slowly cool to 170°C at a rate of 1°C / min, add inorganic filler, increase the speed to 10,000 r / min and continue stirring for 3 hours. After high-speed stirring, adjust the speed to 800 r / min, add anti-stripping agent, and stir at a constant temperature of 170°C for 2 hours to obtain the quick-strength and high-toughness asphalt.
[0032] Example 2 The preparation method of the inorganic filler is as follows, S1.1: Quartz sand and limestone powder were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A, wherein the particle size of the mixture A was 200 mesh; S1.2: The polyester fiber and the PLA fiber were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture B, wherein the particle size of the mixture B was 200 mesh; S1.3: Mix mixture A and mixture B in a mass ratio of 1:1, disperse in 30% by mass fraction of silane coupling agent KH550, with a solid-liquid mass ratio of 1:1, add 1wt% polyethylene glycol 4000, stir at a speed of 200r / min, raise the temperature to 50℃ while stirring, continue stirring for 0.5h after constant temperature, filter, and dry at 80℃ for 16h to obtain mixture C; S1.4: Transfer the mixture C to 200°C and roast for 2h. Slowly cool it to room temperature and grind it again at a cooling rate of 2°C / min to obtain an inorganic filler with a particle size of 500 mesh.
[0033] The preparation method of the anti-stripping agent is as follows: Rosin, beeswax and terpene resin were mixed in a mass ratio of 1:1:1, heated to 110°C, stirred at 150 r / min after constant temperature, and stirred for 1 hour. 2 wt% of silane coupling agent KH550 was added, and stirring was continued for 0.5 hours to obtain the anti-stripping agent.
[0034] A method for preparing a fast-strengthening high-toughness asphalt, the method for preparing the fast-strengthening high-toughness asphalt is as follows: S2.1: Heat the base asphalt to 135°C and stir at a speed of 5500 r / min for 2 h; S2.2: Add SBS and OPE in proportion, increase the speed to 8000r / min, and slowly increase the temperature to 185℃ at a rate of 2℃ / min. Stir for 0.5h after constant temperature. S2.3: After stirring, slowly cool to 175°C at a rate of 1°C / min, add inorganic filler, increase the speed to 10000r / min and continue stirring for 2h. After high-speed stirring, adjust the speed to 800r / min, add anti-stripping agent, stir at a constant temperature of 175°C for 1h to obtain the quick-strength and high-toughness asphalt.
[0035] Example 3 The preparation method of the inorganic filler is as follows, S1.1: Quartz sand and limestone powder were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A, wherein the particle size of the mixture A was 200 mesh; S1.2: The polyester fiber and the PLA fiber were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture B, wherein the particle size of the mixture B was 200 mesh; S1.3: Mix mixture A and mixture B in a mass ratio of 3:1, disperse in 50% by mass fraction of silane coupling agent KH550, with a solid-liquid mass ratio of 1:1, add 1wt% polyethylene glycol 2000, stir at a speed of 200r / min, raise the temperature to 50℃ while stirring, continue stirring for 0.5h after constant temperature, filter, and dry at 80℃ for 16h to obtain mixture C; S1.4: Transfer the mixture C to 200°C and roast for 2h. Slowly cool it to room temperature and grind it again at a cooling rate of 2°C / min to obtain an inorganic filler with a particle size of 500 mesh.
[0036] The preparation method of the anti-stripping agent is as follows: Rosin, beeswax and terpene resin were mixed in a mass ratio of 1:1:1, heated to 110°C, stirred at 150 r / min after constant temperature, and stirred for 1 hour. 2 wt% of silane coupling agent KH550 was added, and stirring was continued for 0.5 hours to obtain the anti-stripping agent.
[0037] A method for preparing a fast-strengthening high-toughness asphalt, the method for preparing the fast-strengthening high-toughness asphalt is as follows: S2.1: Heat the base asphalt to 155°C and stir at a speed of 4500 r / min for 1 h; S2.2: Add SBS and OPE in proportion, increase the speed to 8000r / min, and slowly increase the temperature to 180℃ at a rate of 2℃ / min. Stir for 0.5h after constant temperature. S2.3: After stirring, slowly cool to 175°C at a rate of 1°C / min, add inorganic filler, increase the speed to 10000r / min and continue stirring for 2h. After high-speed stirring, adjust the speed to 800r / min, add anti-stripping agent, stir at a constant temperature of 175°C for 2h to obtain the quick-strength and high-toughness asphalt.
[0038] Comparative Example 1 In this comparative example, polyester fiber and PLA fiber were not added during the preparation of the inorganic filler, and the remaining steps were consistent with those of Example 1.
[0039] Comparative Example 2 In this comparative example, no silane coupling agent KH550 was added during the preparation of the inorganic filler, and the remaining steps were consistent with those of Example 1.
[0040] Comparative Example 3 In this comparative example, no rosin was added during the preparation of the anti-stripping agent, and the remaining steps were consistent with those of Example 1.
[0041] Comparative Example 4 In this comparative example, beeswax was not added during the preparation of the anti-stripping agent, and the remaining steps were consistent with those of Example 1.
[0042] Comparative Example 5 In this comparative example, no terpene resin was added during the preparation of the anti-stripping agent, and the remaining steps were consistent with those of Example 1.
[0043] The performance tests of the embodiments and comparative examples were carried out, the needle penetration test (25°C) was carried out according to T0604-2011, the ductility test (5°C) was carried out according to T0605-2011, the softening point test was carried out according to T0606-2011, the Brookfield rotation viscosity test (135°C) was carried out according to T0625-2011, the elastic recovery test (25°C) was carried out according to T0662-2011, and the toughness test (25°C) was carried out according to T0624-2011. The experimental results are summarized in the following table.
[0044] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A fast-strengthening and high-toughness asphalt, characterized in that: The raw materials for preparing the fast-strengthening high-toughness asphalt are as follows: by mass percentage, 75-85% of base asphalt, 5-12% of polystyrene butadiene copolymer SBS, 3-8% of oxidized polyethylene OPE, 2-5% of inorganic filler, 1-3% of anti-stripping agent, and 2-6% of rubber oil; The preparation method of the inorganic filler is as follows: S1.1: Quartz sand and limestone powder were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A; S1.2: The polyester fiber and the polylactic acid PLA fiber were mixed in a mass ratio of 2:1, and ground in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture B; S1.3: Mix mixture A and mixture B in a mass ratio of (1-3):1, disperse in 30-50% by mass fraction of silane coupling agent KH550, with a solid-liquid mass ratio of 1:1, add 1wt% polyethylene glycol, stir at a speed of 200r / min, raise the temperature to 50°C while stirring, continue stirring for 0.5h after constant temperature, filter, and dry at 80°C for 16h to obtain mixture C; S1.4: The mixture C is transferred to 200°C and calcined for 2h. After slowly cooling to room temperature, it is ground again to obtain an inorganic filler with a particle size of 500 mesh.
2. The fast-strengthening and high-toughness asphalt according to claim 1, characterized in that: The base asphalt is No. 70 petroleum asphalt.
3. The fast-strengthening and high-toughness asphalt according to claim 1, characterized in that: The preparation method of the anti-stripping agent is as follows: rosin, beeswax and terpene resin are mixed in a mass ratio of 1:1:1, heated to 110°C, stirred at 150r / min after constant temperature, and the stirring time is 1h, 2wt% silane coupling agent KH550 is added, and stirring is continued for 0.5h to obtain the anti-stripping agent.
4. The fast-strengthening and high-toughness asphalt according to claim 1, characterized in that: The particle size of the mixture A in S1.1 is 200 mesh.
5. The fast-strengthening and high-toughness asphalt according to claim 1, characterized in that: The particle size of the mixture B in S1.2 is 200 mesh.
6. The fast-strengthening and high-toughness asphalt according to claim 1, characterized in that: The number average molecular weight of the polyethylene glycol added in S1.3 is in the range of 2000 to 4000.
7. The fast-strengthening and high-toughness asphalt according to claim 1, characterized in that: The slow cooling rate in S1.4 is 2°C / min.
8. A method for preparing a fast-strengthening high-toughness asphalt, based on the fast-strengthening high-toughness asphalt according to any one of claims 1 to 7, characterized in that: The method for preparing the rapid-strength high-toughness asphalt is as follows: S2.1: Heat the base asphalt to 135-155°C and stir at a speed of 4500-5500 r / min for 1-2 hours; S2.2: Add SBS and OPE in proportion, increase the speed to 8000r / min, and slowly increase the temperature to 180-185℃, and stir for 0.5-1h after constant temperature; S2.3: After stirring, slowly cool to 170-175°C, add inorganic filler, increase the speed to 10,000 r / min and continue stirring for 2-3 hours. After high-speed stirring, adjust the speed to 800 r / min, add anti-stripping agent, stir at a constant temperature of 170-175°C for 1-2 hours to obtain the quick-strength and high-toughness asphalt.
9. The method for preparing a fast-strengthening and high-toughness asphalt according to claim 8, characterized in that: The rate of slow heating in S2.2 is 2°C / min.
10. The method for preparing a fast-strengthening and high-toughness asphalt according to claim 8, characterized in that: The slow cooling rate in S2.3 is 1°C / min.